Patterns of Substrate Bioerosion by Excavating Sponges From the Southwest and Central Pacific Ocean - Pohler, Susanne M. L.; Feussner, Klaus; Kaniki, Henry V.; Rashni, Bindiya; Wendt, Hans (Frontiers in Earth Science, 2022)
Reef rubble from a number of locations in the southwest and central Pacific (Fiji, Kiribati, Solomon Islands) was surveyed for its level of infestation with bioeroding sponges. The assessment was performed by random sampling of reef rubble in shallow water ranging from intertidal to subtidal down to 15 m of water depth. It was found that essentially four styles of bioerosion prevailed: 1) small cavities with roundish cross sections commonly produced by Pione spp. and Cliona cf. macgeachii Holmes; 2) large cavities in the order of cm-size are for example produced by Aka spp., Cliothosa spp., Cliona cf. janitrix Topsent, Cliona cf. ensifera Sollas, and others; 3) multiple etchings which can degrade the interior of coral rubble on a scale of a few cm in diameter are typically produced by both, Cliona orientalis and C. celata species complexes; and 4) large hadromerid sponges are capable of eroding into solid reef rock and produce silt-, sand-, and pebble-sized fragments. Observed was the activity of Spheciospongia solida (Ridley & Dendy) and S. cf. inconstans var. digitata Dendy. These large clionaid sponges are the most efficient eroders on the reef. Species of Pione are abundant at all sites from intertidal to subtidal, and although they are weak bioeroders, they may be the most destructive by number.